Predictive value of ALDH1 and CD44 positivity for radiotherapy response and prognosis in early-stage glottic laryngeal squamous cell carcinoma - Surmelioglu, Ozgur; Erdogan, Kıvılcım; Dagkiran, Muhammed; Ozdemir, Suleyman; Tarkan, Ozgur; Uguz, Aysun (Polish Journal of Pathology, 2022)
To evaluate the predictive value of CD44 and aldehyde dehydrogenase 1 (ALDH1) expression for prognosis and radiotherapy (RT) response in patients with early-stage laryngeal cancer receiving RT. Forty-four patients with early-stage laryngeal cancer diagnosed between 2002 and 2016 were included in the study. The correlation between RT response and pre-treatment immunohistochemical ALDH1 and CD44 staining was evaluated. In addition, survival times were compared between groups. The mean age of the 44 patients was 59.8 ±9.0 (43-81) years and 41 were male. There were 20 patients in the non-recurrent group (all men) and 24 patients in the recurrent group (21 men). Immunohistochemical positivity for ALDH1 was found to be a significant risk factor for RT failure (p = 0.0001), whereas CD44 positivity (p = 0.114) and age group (p = 0.287) were not significant. ALDH1 positivity was identified as a significant predictor of DFS and RT sensitivity, while CD44 positivity did not differ according to RT response.